Improved pulmonary 129Xe ventilation imaging via 3D‐spiral UTE MRI. Issue 1 (1st December 2019) - Willmering, Matthew M.; Niedbalski, Peter J.; Wang, Hui; Walkup, Laura L.; Robison, Ryan K.; Pipe, James G.; Cleveland, Zackary I.; Woods, Jason C.
Abstract : Purpose: Hyperpolarized 129 Xe MRI characterizes regional lung ventilation in a variety of disease populations, with high sensitivity to airway obstruction in early disease. However, ventilation images are usually limited to a single breath‐hold and most‐often acquired using gradient‐recalled echo sequences with thick slices (~10‐15 mm), which increases partial‐volume effects, limits ability to observe small defects, and suffers from imperfect slice selection. We demonstrate higher‐resolution ventilation images, in shorter breath‐holds, using FLORET (Fermat Looped ORthogonally Encoded Trajectories), a center‐out 3D‐spiral UTE sequence. Methods: In vivo human adult ( N = 4; 2 healthy, 2 with cystic fibrosis) 129 Xe images were acquired using 2D gradient‐recalled echo, 3D radial, and FLORET. Each sequence was acquired at its highest possible resolution within a 16‐second breath‐hold with a minimum voxel dimension of 3 mm. Images were compared using 129 Xe ventilation defect percentage, SNR, similarity coefficients, and vasculature cross‐sections. Results: The FLORET sequence obtained relative normalized SNR, 40% greater than 2D gradient‐recalled echo ( P = .012) and 26% greater than 3D radial ( P = .067). Moreover, the FLORET images were acquired with 3‐fold‐higher nominal resolution in a 15% shorter breath‐hold. Finally, vasculature was less prominent in FLORET, likely due to diminished susceptibility‐induced dephasing at shorter TEs afforded by UTE sequences. Conclusion: The FLORET sequence yields higher SNR for a given resolution with a shorter breath‐hold than traditional ventilation imaging techniques. This sequence more accurately measures ventilation abnormalities and enables reduced scan times in patients with poor compliance and severe lung disease.